Ovol2 promoter mutations in mice and human illuminate species-specific phenotypic divergence - Sunny, Sweetu Susan; Lachova, Jitka; Kasparek, Petr; Palkova, Marcela; Spoutil, Frantisek; Prochazka, Jan; Sedlacek, Radislav; Liskova, Petra; Kozmik, Zbynek (Human molecular genetics, 2024)
Pathogenic variants in the highly conserved OVOL2 promoter region cause posterior polymorphous corneal dystrophy (PPCD) 1 by inducing an ectopic expression of the endothelial OVOL2 mRNA. Here we produced an allelic series of Ovol2 promoter mutations in the mouse model including the heterozygous c.-307T>C variant (RefSeq NM_021220.4) causing PPCD1 in humans. Despite the high evolutionary conservation of the Ovol2 promoter, only some alterations of its sequence had phenotypic consequences in mice. Four independent sequence variants in the distal part of the Ovol2 promoter had no significant effect on endothelial Ovol2 mRNA level or caused any ocular phenotype. In contrast, the mutation c.-307T>C resulted in increased Ovol2 expression in the corneal endothelium. However, only a small fraction of adult mice c.-307T>C heterozygotes developed ocular phenotypes such as irido-corneal adhesions, and corneal opacity. Interestingly, phenotypic penetrance was increased at embryonic stages. Notably, c.-307T>C mutation is located next to the Ovol1/Ovol2 transcription factor binding site. Mice carrying an allele with a deletion encompassing the Ovol2 binding site c.-307_-320del showed significant Ovol2 gene upregulation in the cornea endothelium and exhibited phenotypes similar to the c.-307T>C mutation. In conclusion, although the mutations c.-307T>C and -307_-320del lead to a comparably strong increase in endothelial Ovol2 expression as seen in PPCD1 patients, endothelial dystrophy was not observed in the mouse model, implicating species-specific differences in endothelial cell biology. Nonetheless, the emergence of dominant ocular phenotypes associated with Ovol2 promoter variants in mice implies a potential role of this gene in eye development and disease.
Keywords: messenger RNA; Corneal Dystrophies, Hereditary; Disease Models, Animal; rohovkový endotel; Mice; Adult; Transcription Factors; fenotyp; dědičné dystrofie rohovky; Ovol2; transkripční faktory; Phenotype; corneal endothelium; modely nemocí na zvířatech; cornea; RNA, Messenger; zvířata; Humans; Endothelium, Corneal; myši; pathogenic variant; dospělí; PPCD1; lidé; Animals